The relationship between individual characteristics, sweet drink consumption, sleep quality, and stress levels with Impaired Fasting Glucose (IFG) levels among high school adolescents - Zafirah, Amalia Nur; Yamani, Laura Navika (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Prediabetes typically appears in the early stages of T2DM development, including IFG as one of the indicators. Globally, the prevalence of IFG is estimated to be increasing in low-income or developing countries, as Southeast Asia is the largest contributor. However, there is limited information on IFG in each age group, including adolescents, who are highly risk to adopting unhealthy lifestyles. This study aims to evaluate fasting blood glucose levels measured from capillary blood samples of high-school adolescents, aged 15–19 years, and its relationship with individual characteristics, consumption of sweetened beverages, sleep quality, and stress levels. Method: This quantitative study employed a cross-sectional design. A total of 251 participants were selected using stratified and simple random sampling techniques. Data were collected through self-administered questionnaires, which included a demographic questionnaire, FFQ, PSQI, and DASS-42. In addition, direct measurements of height, weight, and fasting capillary blood glucose levels were conducted using standardized tools, including a glucometer. Data analysis involved univariate and bivariate, the chi-square test used to assess associations, conducted using SPSS version 27. Result: The study found that the prevalence of IFG among adolescents in the Alun-Alun Gresik Community Health Center (Puskesmas) working area was relatively high, about 32.3%. A significant impact was observed between BMI (p<0.001), family history of diabetes (p<0.001), consumption of sweet drinks (p=0.004), and age group (p=0.019) towards the incidence of IFG. In contrast, no significant relationship was identified between gender (p=0.643), sleep quality (p=0.973), or stress levels (p=0.635). Conclusion: These results underscore the need for increased awareness, early identification, and preventive interventions targeting at-risk adolescents to mitigate the progression to type 2 diabetes. (www.actabiomedica.it)